Relasi Terorisme dan Media - Fajar Junaedi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2010)
Terrorism is the major issue in the recent years. As political communications forms, terrorism can only have significance as a communication act if the action of terrorism group transmitted through the mass media to the large audience. Terrorist did violence and other terror actions in order to get support from public, make fearness for institutional government and raise funding from their supporters.